Non-invasive ventilation in obesity hypoventilation syndrome without severe obstructive sleep apnoea. Issue 10 (12th July 2016) - Masa, Juan F; Corral, Jaime; Caballero, Candela; Barrot, Emilia; Terán-Santos, Joaquin; Alonso-Álvarez, Maria L; Gomez-Garcia, Teresa; González, Mónica; López-Martín, Soledad; De Lucas, Pilar; Marin, José M; Marti, Sergi; et al.
Abstract : Background: Non-invasive ventilation (NIV) is an effective form of treatment in patients with obesity hypoventilation syndrome (OHS) who have concomitant severe obstructive sleep apnoea (OSA). However, there is a paucity of evidence on the efficacy of NIV in patients with OHS without severe OSA. We performed a multicentre randomised clinical trial to determine the comparative efficacy of NIV versus lifestyle modification (control group) using daytime arterial carbon dioxide tension (PaCO2 ) as the main outcome measure. Methods: Between May 2009 and December 2014 we sequentially screened patients with OHS without severe OSA. Participants were randomised to NIV versus lifestyle modification and were followed for 2 months. Arterial blood gas parameters, clinical symptoms, health-related quality of life assessments, polysomnography, spirometry, 6-min walk distance test, blood pressure measurements and healthcare resource utilisation were evaluated. Statistical analysis was performed using intention-to-treat analysis. Results: A total of 365 patients were screened of whom 58 were excluded. Severe OSA was present in 221 and the remaining 86 patients without severe OSA were randomised. NIV led to a significantly larger improvement in PaCO2 of −6 (95% CI −7.7 to −4.2) mm Hg versus −2.8 (95% CI −4.3 to −1.3) mm Hg, (p<0.001) and serum bicarbonate of −3.4 (95% CI −4.5 to −2.3) versus −1 (95% CI −1.7 to −0.2 95% CI) mmol/L (p<0.001). PaCO2 change adjusted for NIV compliance did not further improve the inter-group statistical significance. Sleepiness, some health-related quality of life assessments and polysomnographic parameters improved significantly more with NIV than with lifestyle modification. Additionally, there was a tendency towards lower healthcare resource utilisation in the NIV group. Conclusions: NIV is more effective than lifestyle modification in improving daytime PaCO2, sleepiness and polysomnographic parameters. Long-term prospective studies are necessary to determine whether NIV reduces healthcare resource utilisation, cardiovascular events and mortality. Trial registration number: NCT01405976; results.